Organising Pedagogical Activities for Sleep - Sardi, Hara; Agelidou, Evangelia (Advances in Social Sciences Research Journal, 2014)
The aim of this study is to highlight the importance of sleep in the memory - learning procedure, through pedagogical activities. For this purpose a) there was investigated the relationship between sleep and memory – learning through contemporary research data from the Neuroscience and b) pedagogical activities were designed and proposed Recent studies support that sleep is affecting the daily activities, the physical and mental health and it plays a significant role in memory’s consolidation and furthermore in learning. Research data support that the problem sleep lack is fundamental in adolescence. Taking into consideration that: -The recent findings of the positive role of a sufficient and qualitative sleep in memory – learning are not widely known in pupils / students. -The learning process concerns directly pupils / students as it is related to their personal progress and prosperity. We thought that it would be meaningful to accomplish this work and more specifically: a) to accomplish a didactic transformation of data from the field of Neuroscience related to sleep and memory - learning. b) to propose specific examples such as activities of a role playing, synthesis of a questionnaire and several dramatizations.